Rettens landskap Tingsteder og rettskretser i Viken i jernalder og middelalder - Ødegaard, Marie (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
What gave rise to the Norse legal system? When? And where were the meeting places under this system located? These are questions that have long remained unanswered in Norwegian and Northern European history. An overriding theme of the book is establishing when this legal system arose and how it developed over time at the local and regional levels. Central topics include the localization of assembly sites in the landscape and how these sites became important to the consolidation of power structures and, later on, the royal system of governance. The 'things' are discussed in relation to successive political and economic structures as well as the influence of conditions within settlements and society. The book also looks at the assembly sites in their various contexts regarding localization and importance in the region, and in connection with the system's development in Northern Europe. The Landscape of the Law provides extensive insight into the places where law and justice and related legal matters were decided in Viken. This is an aspect of Norway's territorial division that has not been addressed in prior research. The book is relevant for researchers and history and archeology students working in such areas as legal and religious history, administrative jurisdictions, and state-formation processes, as well as local historians and other readers interested in cultural history.